Structural changes in lignocellulosic biomass during activation with ionic liquids comprising 3-methylimidazolium cations and carboxylate anions - Moyer, Preenaa (Biotechnol Biofuels, 2018)
BACKGROUND: Lignocellulosic biomass requires either pretreatment and/or fractionation to recover its individual components for further use as intermediate building blocks for producing fuels, chemicals, and products. Numerous ionic liquids (ILs) have been investigated for biomass pretreatment or fractionation due to their ability to activate lignocellulosic biomass, thereby reducing biomass recalcitrance with minimal impact on its structural components. In this work, we studied and compared 1-allyl-3-methylimidazolium formate ([AMIM][HCOO]) to the commonly used 1-ethyl-3-methylimidazolium acetate ([EMIM][CH(3)COO]) for its potential to activate hybrid poplar biomass and enable high cellulose and hemicellulose enzymatic conversion. Although [EMIM][CH(3)COO] has been widely used for activation, [AMIM][HCOO] was recently identified to achieve higher biomass solubility, with an increase of 40% over [EMIM][CH(3)COO]. RESULTS: Since IL activation is essentially an early stage of IL dissolution, we assessed the recalcitrance of [EMIM][CH(3)COO] and [AMIM][HCOO]-activated biomass through a suite of analytical tools. More specifically, Fourier transform infrared spectroscopy and X-ray diffraction showed that activation using [AMIM][HCOO] does not deacetylate hybrid poplar as readily as [EMIM][CH(3)COO] and preserves the crystallinity of the cellulose fraction, respectively. This was supported by scanning electron microscopy and enzymatic saccharification experiments in which [EMIM][CH(3)COO]-activated biomass yielded almost twice the cellulose and hemicellulose conversion as compared to [AMIM][HCOO]-activated biomass. CONCLUSION: We conclude that the IL [AMIM][HCOO] is better suited for biomass dissolution and direct product formation, whereas [EMIM][CH(3)COO] remains the better IL for biomass activation and fractionation.